Topical treatment of actinic keratosis with imiquimod 5% cream - T.N.A. Garcez; D.G. Gerardi; K.C. Ferreira; C.S. Cardoso; P.D. Möschbacher; E.A. Contesini (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2012)
The viability and the efficiency of imiquimod 5% cream in a cat which suffered from nasal actinic keratosis were evaluated. The procedures were carried out at home by the owners themselves. Six packets of the cream were used, one per week, in three consecutive daily applications, with a four-day interval (without treatment). The cytological results were negative for neoplastic cells 30 days after the end of the treatment. A clinical revision was conducted 18 months later and the animal showed no signs of recurrence. The cream proved to be safe and efficient. There are no reports regarding efficiency in animals concerning the treatment with imiquimod 5% cream and also regarding other effects related to this treatment. A case report presenting a positive response can reveal with terapeutical possibilities that it would be easily available and applicable for all professionals. In the future it would be a new alternative to avoid progressions of this kind of neoplasia which is often observed in the small animal clinic.